"We Are Family" for Promoting Student Wellbeing and Advancing SDG 4: A Multi-Site Case Study in Islamic Junior High Schools - Zuhrotul Mufidah; Erny Roesminingsih; Karwanto Karwanto (Journal of Current Studies in SDGs, 2026)
Objective: To investigate how student wellbeing is realized in Islamic junior high schools, examine the implementation of the We Are Family (WAF) school culture program, identify the character outcomes generated through the program, and develop a conceptual model of a wellbeing-based school culture.  Method: A qualitative multi-site case study design was employed at two Islamic junior high schools in Sidoarjo. Data were collected through in-depth interviews, participatory observations, and document analysis involving principals, vice principals, program teachers, and students. The data were analyzed using the interactive model of Miles, Huberman, including data condensation, data display, and conclusion drawing, followed by cross-site analysis to identify convergent and divergent patterns. Results:  The findings reveal that student wellbeing is realized through four interconnected dimensions: academic, psychological, social, and spiritual wellbeing. The WAF program operates through a relational culture characterized by familial climate, emotional-spiritual support, collective character development, and school-family collaboration. The program contributes to the development of responsibility, empathy, value-based discipline, mutual respect, sense of belonging, and independence. Cross-site analysis further identifies six essential elements of a wellbeing-based school culture: values-based environment, transformational leadership, psychological safety, dialogic communication, developmental discipline, and school-family collaboration.  Novelty: Contributes to SDGs 4 by porposing the WAF School Culture Model and introduces spiritual wellbeing as a distinct fourth dimension of student wellbeing, extending existing wellbeing frameworks by integrating organizational culture, positive psychology, character education, and faith-based educational perspectives into a comprehensive school wellbeing framework.